(3GSGdjH OYe bOQGJ GLgRI GdJWhjQ GdGOGQj aj GdOhd GdfGejI (B/s - (3GdCee GdeJMOIs ((3GdCQOf(B: s (3GdefXeI GdYQHjI ddJfejI GdGOGQjI(B, s, 1994)
(3JbQjQ GLJeGY GdNHQGA (B11-15 (3OjSeHQ (B1989 (3e, HQhcSd GdLRA GdChd (B: (3JbQjQ Yf GdGLJeGY (B: (3GdXQha GdHjFjI GdeJZjQI GdJj JYed ajgG CLgRI GdJWhjQ GdEOGQj (B: (3OhQ CLgRI GdJWhjQ GdEOGQj (B: (3bjhO heYhbGJ aYGdjI CLgRI GdJWhjQ GdEOGQj (B: (3GdJQJjHGJ GdgjcdjI dCLgRI GdJWhjQ GdEOGQj(B-(3GdLRA GdKGfj (B: (3GdChQGb GdafjI (B: (3RjGOI aYGdjI fXGe GdEOGQI GdYGeI (B: (3GgJeGeGJ hbVGjG (B: (3GdCOhGQ hGdeSDhdjGJ GdeJZjQI ddOhdI (B: (3GdCKQ Ydi GdbWGY GdYGe (B: (3GdMGLI Edi GdJOQjH EOGQj (B: (3YhGed HjFjI CNQi (B: (3JWhjQ eDSSGJ GdbWGY GdYGe (B: (3GdWdH Ydi GdegGQGJ GdEOGQjI (B: (3GdJWhjQ GdEOGQj aj GdOhd GdfGejI (B: (3eONd ehbaj dJcGed fXQjI GdEOGQI hGdSHGb (B: (3OhQ GdEUdGM GdEOGQjI aj GdJfejI (B: (3GdbOQGJ GdEOGQjI (B: (3GdMdbI GdVYjaI aj SdSdI GdJfejI (B: (3eYhbGJ JMSjf aYGdjI EOGQI GdJfejI (B: (3GdJWhjQ GdEOGQj GdcaGAI GdafjI hCcKQ (B: (3GdeNd Gdehbaj ddJWhjQ GdEOGQj (B: (3GdeJWdHGJ GdeaGgjejI dGSJNOGe GdeONd Gdehbaj aj GdJWhjQ GdEOGQj (B: (3JcGed EOGQI GdcaGAI hGdEOGQI GdehbajI (B: (3GdJUeje hGdYedjGJ GdJfXjejI hJTjLY GdcaGAI (B: (3eOGNd JNajV Gdbhi GdYGedI (B: (3GdGHJcGQ aj HjFI GdfOQI(B.s
Keywords: (3GOGQg MchejIs; (3GdGOGQg GdYGeIs; (3GdJfejI GdEOGQjIs; (3GdOhd GdfGejIs